Drunkorexia: An Empirical Investigation among Australian Female University Students. (30th June 2016) - Knight, Alissa; Castelnuovo, Gianluca; Pietrabissa, Giada; Manzoni, Gian Mauro; Simpson, Susan
Abstract : Objective: Anecdotal claims insinuate that female Australian university students may be engaging in a new type of hazardous phenomena called "drunkorexia" (i.e., using disordered eating to compensate for planned binge drinking). However, to date, this conjecture has not been validated by empirical evidence. The primary aim of the present study was to estimate the frequency of drunkorexia behaviours in a population of non‐clinical Australian undergraduate female university students. A secondary aim was to explore whether drunkorexia may be a stand‐alone problem, separate from traditional eating disorders. Methods: One hundred and thirty‐six healthy female Australian undergraduate university students between 18 and 25 years ( M= 21.32, SD= 2.73) completed the self‐report Compensatory Eating and Behaviors in Response to Alcohol Consumption Scale to screen for drunkorexia symptomatology. Results: Among the study sample, 57.7% ( n = 85) of Australian female university students reported drunkorexia‐type behaviours 25% of the time or more, while 27.2% ( n = 37) reported no drunkorexia‐type behaviour. In addition, 16.2 8% ( n = 22) of the participants reported engaging in characteristic drunkorexic behaviours to specifically offset ingested alcohol calories while not engaging in such behaviours routinely for any other reason or with any other type of food or drink. Conclusions: Results of this study add preliminary empirical evidence that a number of Australian female university students are employing drunkorexia‐type behaviours as a way to drink alcohol without the concern of ingested calories. Further evidence is needed to definitively conclude that drunkorexia represents a distinctive problem that is separate from traditional eating disorders.